Assessment of measuring techniques to study the deflection of ceramic tile during ballistic impact - Santos, Peter Daniel Gonçalves (2014)
Dissertação de Mestrado Integrado em Engenharia Mecânica apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra